The Relationship Between Pocket Money and Breakfast Habits with Nutritional Status Among Students at SDN Adiarsa Barat IV, Karawang Regency - Syifa Kania Khaerunisa; Milliyantri Elvandari; Linda Riski Sefrina (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Nutritional status among elementary school children is an important indicator of health, growth, and development, and may be influenced by dietary behaviors such as breakfast habits and pocket money. This study aimed to analyze the relationship between pocket money and breakfast habits with the nutritional status of students at SDN Adiarsa Barat IV, Karawang Regency. This study used a quantitative cross-sectional design involving 30 elementary school students selected as respondents. Data on pocket money and breakfast habits were collected using questionnaires, while nutritional status was determined based on body mass index (BMI). Data analysis was performed using the Spearman correlation test. The results showed that there was no significant relationship between pocket money and nutritional status (p-value = 0.181; r = 0.338). However, breakfast habits were significantly associated with nutritional status (p-value = 0.003; r = -0.527). Students with poor breakfast habits were more likely to have overweight nutritional status, while students with good breakfast habits tended to have normal nutritional status. These findings indicate that breakfast habits play an important role in maintaining the nutritional status of school-aged children. Therefore, schools and parents should encourage healthy breakfast habits and balanced eating patterns to prevent nutritional problems among elementary school children.